Analisis Penggunaan Tiktok Sebagai Media Promosi Dalam Persepsi Pelaku Umkm Sepatu di Desa Campaka, Kecamatan Cimaung, Kabupaten Bandung: Analysis of the Use of TikTok as a Promotional Medium in the Perceptions of Shoe SME Operators in Campaka Village, Cimaung Subdistrict, Bandung Regency - Ervina Tasani; Dudi Sudirman; Fajar Sulaiman (Institut Agama Islam Persis Bandung, 2025)
The advancement of digital technology has encouraged Micro, Small, and Medium Enterprises (MSMEs) to utilize social media, particularly TikTok, as a means of product promotion. This study aims to analyze the use of TikTok as a promotional medium and the perceptions of MSME footwear entrepreneurs in Campaka Village, Cimaung Sub-district, Bandung Regency, focusing on three business owners Zapato Official, Azfiq27, and Military Boots Berkah Store who operate within the same product ecosystem yet achieve different sales outcomes. This study employs a descriptive qualitative approach using a case study method. Data were collected through in-depth interviews, observation, and documentation, then analyzed using the interactive model of Miles and Huberman, comprising data reduction, data display, and conclusion drawing. Data validity was examined through technique triangulation. The results show that all three MSMEs utilize four main TikTok features content marketing, live streaming, TikTok Ads, and affiliate marketing in an integrated manner to expand market reach and increase sales. The entrepreneurs hold a positive perception of TikTok as an effective promotional platform, despite facing challenges such as algorithm changes, price competition, capital requirements, and platform administrative costs. These findings indicate that promotional success is determined not only by shared product sources, but also by how entrepreneurs interpret and implement promotional strategies based on their individual perceptions